Air–vacuum transfer; establishing traceability to the new kilogram. (28th September 2016) - Davidson, Stuart; Berry, James; Abbott, Patrick; Marti, Kilian; Green, Richard; Malengo, Andrea; Nielsen, Lars
Abstract: The redefinition of the kilogram, along with another three of the base units of the International System of Units (SI), is scheduled for 2018. The current definition of the SI unit of mass assigns a mass of exactly one kilogram to the International Prototype of the kilogram, which is maintained in air and from which the unit is disseminated. The new definition, which will be from the Planck constant, involves the realisation of the mass unit in vacuum by the watt balance or Avogadro experiments. Thus, for the effective dissemination of the mass unit from the primary realisation experiments to end users, traceability of mass standards transferred between vacuum and air needs to be established and the associated uncertainties well understood. This paper describes a means of achieving the link between a unit realised in vacuum and standards used in air, and the ways in which their use can be optimised. It also investigates the likely uncertainty contribution introduced by the vacuum–air transfer process.